“I can sit on the beach and punt through my mobile phone”: The influence of physical and online environments on the gambling risk behaviours of young men - Deans, E.; Thomas, S.; Daube, Mike; Derevensky, J. (Pergamon Press, 2016)
© 2016 Elsevier Ltd. Gambling is rapidly emerging as an important public health issue, with gambling products causing considerable health and social harms to individuals, families and communities. Whilst researchers have raised concerns about online wagering environments, few studies have sought to explore how factors within different gambling environments (both online and land-based) may be influencing the wagering, and more broadly the gambling risk behaviours of young men. Using semi-structured interviews with 50 Australian men (20–37 years) who gambled on sport, we explored the ways in which online and land-based environments may be risk-promoting settings for gambling. This included the appeal factors associated with gambling in these environments, factors that encouraged individuals to gamble, and factors that encouraged individuals to engage in different, and more harmful types of gambling. Interviews were conducted over the course of a year (April 2015 – April 2016). We identified a number of situational and structural factors that promoted risky gambling environments for young men. In the online environment, gambling products had become exceedingly easy to access through mobile technologies, with young men subscribing to multiple accounts to access industry promotions. The intangibility of money within online environments impacted upon risk perceptions. In land-based environments, the social rituals associated with peer group behaviour and sport influenced risky patterns of gambling. The presence of both gambling and alcohol in pub environments led individuals to gamble more than they normally would, and on products that they would not normally gamble on. Land-based venues also facilitated access to multiple forms of gambling under the one roof. We identified a number of factors in both land and online environments that when combined, created risk-promoting settings for gambling among young men. By exploring these contextual conditions that give rise to gambling harm, we are better able to advocate for effective public health responses in creating environments that prevent harmful gambling.